PENGABDIAN MASYARAKAT PROYEK EKSPEDISI NUSANTARA (PENA): PELATIHAN PEMBUATAN NUGGET SAYUR SEBAGAI PRODUK OLAHAN BERNILAI GIZI DAN EKONOMIS TINGGI DI TENGAH PANDEMI COVID-19 - Misbahuddin, Angga; Dwi Anggreani, Muthiara; Ajeng Prastika, Dinda; Anisak, Haliza (Universitas PGRI Yogyakarta, 2023)
The COVID-19 pandemic has led to a decrease in people's purchasing power and a reduction in the number of stock items as a form of suppressing household spending. Even so, the community certainly has basic material needs that must be met for daily survival, both in the form of clothing, food, and board, so the Proyek Ekspedisi Nusantara (PENA) is present as a student community that seeks to contribute to the village community in the form of innovation in the use of resources. agricultural products to help the community's economy. Through the creative economy program, PENA seeks to provide training on the use of agricultural products in Ngagrong Village, Boyolali, to be used as nutritious household consumption and economic value innovations which can later be used as business ideas for the community in the future. Through the implementation of the program from pre-activity, implementation of activities to post-activity, it can be concluded that PENA has an important contribution to facilitating the community to be able to take advantage of community agricultural products to reduce household food costs as well as become innovative business creative ideas that have the potential to be developed by the community. Based on the results of testimonies from the mothers of the program training targets, they are very enthusiastic because the use of vegetables as nuggets is a new thing for them and on the one hand it can be a new product to improve children's nutrition and in the future, it can become household economic land Keyword: Covid-19 Pandemic, Creative Economy, Vegetable Nugget, Empowerment, Proyek Ekspedisi Nusantara